STEAM-ing criteria: best criteria for integrating science module with visual art / Siti Soraya Ramli, Siti Zuraida Maaruf and Nabilah Abdullah - Ramli, Siti Soraya; Maaruf, Siti Zuraida; Abdullah, Nabilah (Universiti Teknologi MARA, 2025)
STEM subjects (Science, Technology, Engineering and Mathematics) are widely recognised for a country's development. In Malaysia, integrating arts into STEM education started over 20 years ago with the introduction of KBSR and KBSM. However, some worried that art could divert focus from core STEM skills. This research aims to develop an effective Science module by consulting experts. The module to be developed has gone through the need analysis phase from secondary students and teachers. They faced challenges teaching and learning about energy and sustainability. However, they agreed that arts could aid understanding. In this study, the researcher interviewed six science lecturers, visual art lecturers and curriculum developers in the design and development phase. The semi-structured interview consists of six main questions: Demographics of respondents, Visual Arts Aids, supporting materials, Teaching techniques, Activities, and Exercises suitable to design and develop the Science module. This phase is intended to gather the aspects to be considered in selecting a suitable teaching technique, genre, level, context, the ability of the students, duration of the lesson, and teacher’s experience. The experts shared information on the curriculum aspect, such as evaluation, learning outcome, duration of the implementation, and other resources. Other than that, the experts also offered pieces of information on the design and technical aspects of the module. These interviews are transcribed, and the themes that arise from the interview are used to design the Fuzzy Delphi Method (FDM) instrument. The experts said that thoughtfully integrating visual arts can help students comprehend complex concepts. However, they stressed that art must directly connect to scientific principles. It should complement, not obscure, the STEM focus. With this guidance, the module can leverage the arts to engage students while maintaining rigour. Experts emphasised striking the right balance - using art to reinforce STEM, not displace it. Their insights will shape an integrated curriculum to equip students for the future.